2022
DOI: 10.1093/eurheartj/ehac544.2876
|View full text |Cite
|
Sign up to set email alerts
|

ZNF259 rs964184 variant is associated with dyslipidemia and coronary artery disease in the young population

Abstract: Introduction Coronary artery disease (CAD) is a dynamic inflammatory disease caused by atherosclerosis. GWAS showed that ZNF259 rs964184 encoding zinc finger protein (ZPR1) was associated with dyslipidemia and CAD. Recent research found that ZPR1 transcription is up-regulated in the brain of mice fed a high-fat diet, influencing the cell cycle, apoptosis, and RNA metabolism in neurons. This process at the heart vessels may increase oxidative stress and CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, the 11q23.3 locus, which was identified as novel risk loci for both MDD and MI, was colocalized between MDD, MI, and all quantitative traits of BL, with the same potential shared causal variant rs117937125 identified (mapped gene: ZNF259). Previous studies reported that ZNF259 is associated with dyslipidemia in the whole population and that its transcriptional upregulation increases the sensitivity of coronary endothelial cells to oxidative stress and inflammation 39 . These results highlighted the important role of lipids in the comorbidity.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the 11q23.3 locus, which was identified as novel risk loci for both MDD and MI, was colocalized between MDD, MI, and all quantitative traits of BL, with the same potential shared causal variant rs117937125 identified (mapped gene: ZNF259). Previous studies reported that ZNF259 is associated with dyslipidemia in the whole population and that its transcriptional upregulation increases the sensitivity of coronary endothelial cells to oxidative stress and inflammation 39 . These results highlighted the important role of lipids in the comorbidity.…”
Section: Discussionmentioning
confidence: 98%